ANALISIS OPERASI POMPA CHILLER MENGGUNAKAN FIXED SPEED DRIVE DAN VARIABLE SPEED DRIVE (STUDI KASUS : FOUR SEASON HOTEL JIMBARAN) - Hasan Dedy Sudono; I N. Satya Kumara; WG. Ariastina (Jurnal SPEKTRUM, 2022)
Four Season Jimbaran Hotel is one of the hotels in Bali using a cooling system which isusually called the water chiller. The electrical energy consumption in Four Season Hotel is oneof the factors that increase the use of electrical energy in which the star delta system is stillused to switch on the pump. Along with the electricity rate which keeps increasing every year,the electrical energy consumption in Four Season Hotel can increase the operational cost. It isconcluded that one of the largest electrical energy consumptions is water chiller pump. Chillerpump is a pump used for pushing water flow towards chiller condenser and Air Handling Unit(AHU) when the water chiller system is still active. Starters of the chiller pump used in FourSeason Jimbaran Hotel are inverter and star delta. The method used in conducting research was calculation of the electrical energy requirement and cost in two pumps set by star delta atan initial frequency of 50Hz in water chiller pump 160 TR, compared with inverter system withthe decrease of frequency by 5Hz (45Hz) in water chiller pump 230 TR. Monitoring wasperformed by analyzing the consumption of electrical energy (kWh), temperature (°C), andhumidity (%) in every pump set by every system. In these two pumps, energy consumption(kWh) and cost were compared in daily, weekly, and monthly needs. From the result ofresearch, in inverter system, the frequency reduction by 5Hz in water chiller pump 230 TR cansave electrical energy of 117,120 kWh and the cost of IDR 130,471,680 in the next five years.The comparison analysis of operation of the chiller pump supplied with star delta (fixed speeddrive) with an inverter (variable speed drive) has a difference energy consumption of 117,120kWh in both systems and the difference cost is Rp. 130,471,680.00 in next 5 years.